2013
DOI: 10.4161/bioe.22835
|View full text |Cite
|
Sign up to set email alerts
|

The development of myelin repair agents for treatment of multiple sclerosis

Abstract: Multiple Sclerosis (MS) is an inflammatory demyelinating disorder which affects the central nervous system. Multiple sclerosis treatment has traditionally focused on preventing inflammatory damage to the myelin sheath. Indeed, all currently available disease modifying agents are immunomodulators. However, the limitations of this approach are becoming increasingly clear, leading to the exploration of other potential therapeutic strategies. In particular, targeting the endogenous remyelination system to promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…1 b). In addition, lysoPC is a known potent demyelinating agent either when injected into the spinal cord and other CNS regions or when applied to the PNS 43 45 . Since remyelination in the PNS is efficient and quick but limited by the presence of the demyelinating agent 46 , treatments to lower lysoPC might be considered in GBS therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…1 b). In addition, lysoPC is a known potent demyelinating agent either when injected into the spinal cord and other CNS regions or when applied to the PNS 43 45 . Since remyelination in the PNS is efficient and quick but limited by the presence of the demyelinating agent 46 , treatments to lower lysoPC might be considered in GBS therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies showed that BMPs played an important role in the integrity of BBB [ 14 ]. S1P and S1PRs were involved in cell adhesion, migration, and BBB permeability changes [ 15 ]. In this study, it was found that the expression level of S1PR2 in pericytes of rats transfected with miR-149-5p showed a trend of increasing firstly and then decreasing after acute ischemia perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The general failure of endogenous remyelination and inflammation-related axonal damage lead to accumulated neurological disability [ 2 ]. The current immunomodulating drugs for MS, such as interferon β , glatiramer acetate, and natalizumab, prevent inflammatory damage to the CNS, which do not effectively prevent the progressive clinical neurological decline most likely because they lack a direct action on CNS axons and myelin [ 3 ]. Neural stem cells (NSCs), which can differentiate into various neural cell types [ 2 , 4 ] and have myelinogenic potential [ 5 ] in the injured areas, have been introduced as a promising cell type of replacement therapy.…”
Section: Introductionmentioning
confidence: 99%